EFL Students’ Metacognitive Strategies in Learning Speaking - fitrianingsih; Rahmat Nasrullah; Faridawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to identify the metacognitive strategies students apply in learning to speak. These strategies include planning, monitoring, information management, debugging, and evaluation. The study uses a quantitative approach and distributed questionnaires via Google Forms to 157 respondents. However, only 110 English education students from four different semesters (two, four, six, and eight) at Muhammadiyah University of Kendari were willing to participate. The results show that 41% of students sometimes planning their speaking lessons by reading the instructions carefully before starting the task. Additionally, 39% of students often monitor their comprehension to improve their speaking skills, such as checking whether the presentation objectives are achieved and considering alternative ways to solve speaking problems. For the Information Management strategy, 40% of students often try to translate their talks into their own words for better understanding. Furthermore, 43% of students often follow the Debugging strategy, which involves stopping and repeating when unsure in speaking. In terms of evaluation, 43% of students sometimes evaluate their speaking learning by assessing their performance after speaking comprehension tests and identifying areas for improvement.